2015
DOI: 10.2480/agrmet.d-14-00008
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric O<sub>3</sub>, the nightmare of wild plants: a review study

Abstract: Ambient ozone (O 3 ) poses a growing threat to the global ecosystems due to its high phytotoxicity: it may possibly reduce the productivity of wild plants as well as the species' biodiversity. Asia hosts a remarkable number of wild plant species; thus, studies dealing with Asian species' responses to O 3 are of great importance. We have retrieved, from scientific databases, 195 papers dealing with the response of 473 wild plants species to O 3 . Some species we characterize as "ozonophobic" have been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 106 publications
(190 reference statements)
0
19
0
Order By: Relevance
“…Both plant growth and production as well as plant species biodiversity are significantly disturbed under elevated O 3 conditions, which portends a significant threat to global food security (e.g. Schimidhuber & Tubiello 2007;Feng, Kobayashi, & Ainsworth 2008;Furlan et al 2008;Wittig, Ainsworth, Naidu, Karnosky, & Long 2009;Ainsworth, Yendrek, Sitch, Collins, & Emberson 2012;Wilkinson, Mills, Illidge, & Davies 2012;Agathokleous, Saitanis, & Koike 2015;Cassimiro & Moraes 2016;Freire et al 2017). It is estimated that the average current background concentration of O 3 in the northern hemisphere is around 20-50 nmol mol À1 and O 3 concentrations are predicted to increase due to expected rise in O 3 precursor emissions in the future, implying even greater effects of tropospheric O 3 on global climate change and on atmospheric oxidative status by the end of this century (Vingarzan 2004;Fowler et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both plant growth and production as well as plant species biodiversity are significantly disturbed under elevated O 3 conditions, which portends a significant threat to global food security (e.g. Schimidhuber & Tubiello 2007;Feng, Kobayashi, & Ainsworth 2008;Furlan et al 2008;Wittig, Ainsworth, Naidu, Karnosky, & Long 2009;Ainsworth, Yendrek, Sitch, Collins, & Emberson 2012;Wilkinson, Mills, Illidge, & Davies 2012;Agathokleous, Saitanis, & Koike 2015;Cassimiro & Moraes 2016;Freire et al 2017). It is estimated that the average current background concentration of O 3 in the northern hemisphere is around 20-50 nmol mol À1 and O 3 concentrations are predicted to increase due to expected rise in O 3 precursor emissions in the future, implying even greater effects of tropospheric O 3 on global climate change and on atmospheric oxidative status by the end of this century (Vingarzan 2004;Fowler et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Koike et al, 2013). Thus, O 3 has been regarded as one of the most serious environmental stresses for plants (Matyssek et al, 2012;Agathokleous et al, 2015), concerning with forest decline and tree dieback in East Asia (Izuta and Nakaji, 2003;Izuta, 2006;Watanabe et al, 2005). O 3 concentration usually shows the highest value from spring to summer in northeast Japan (Yamaji et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that elevated O 3 reduces C assimilation and limits the allocation of photosynthates to below-ground (Grantz and Farrar 2000;King et al 2005;Agathokleous et al 2015b). High O 3 levels may weaken the specific rate of inorganic N uptake by roots (Haberer et al 2007) and decrease the standing crop of fine root and sporocarp production of ECM fungi (Kasurinen et al 2005;Andrew and Lilleskov 2009).…”
Section: Effect Of Elevated O 3 On Ecm Symbiosismentioning
confidence: 99%
“…Apparently, though, this relationship is unstable under changing environmental conditions. Current concentrations of O 3 have significant adverse effects on forests (Ashmore 2005;Yamaguchi et al 2011;Agathokleous et al 2015b). Most experiments of O 3 effects on trees are based on an assessment of above-ground parts, and much less is known about below-ground processes (Andersen 2003).…”
Section: Introductionmentioning
confidence: 99%